2020
DOI: 10.1111/vox.12887
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis E viraemia among blood donors: a systematic review

Abstract: Background Hepatitis E virus (HEV) is usually transmitted by faecal-oral route. Recent reports have documented HEV viraemia in donated blood units and HEV transmission through blood transfusion. This systematic review summarizes the available data on prevalence of HEV viraemia in blood donors.Methods Electronic databases were searched on 17 December 2018 to identify full-text English papers reporting original data on prevalence of HEV RNA in donated blood units. Two authors independently extracted the relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
(110 reference statements)
0
17
0
Order By: Relevance
“…Anti‐HEV antibodies serve as a surrogate marker for HEV viraemia. However, in the existing studies, viraemia was equally common in the seropositive and seronegative HEV units; 35 besides that, only a minority of HEV viraemic blood units were seropositive. Therefore, tests for these HEV antibodies are unlikely to be useful for screening donated blood.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Anti‐HEV antibodies serve as a surrogate marker for HEV viraemia. However, in the existing studies, viraemia was equally common in the seropositive and seronegative HEV units; 35 besides that, only a minority of HEV viraemic blood units were seropositive. Therefore, tests for these HEV antibodies are unlikely to be useful for screening donated blood.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, tests for these HEV antibodies are unlikely to be useful for screening donated blood. Moreover, it has previously been reported that HEV‐PCR might be a better indicator than ELISA of acute HEV infection, 36 and the identification of HEV‐RNA also has the advantage of a lower likelihood of being affected by genomic variations of the virus 24,35 …”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis E virus is one of the non-enveloped viruses with increasing incidence in industrialized countries and may have serious clinical courses with chronic hepatitis and neurological complications, particularly in immunocompromised patients [ 66 ]. Mini pool nucleic acid amplification testing is currently used in blood manufacturing establishments for screening, but it can only detect high viremia [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…HEV‐RNA prevalence rates in blood donors who may have acquired the infection by consuming insufficiently cooked meat from infected animals varies widely between different geographical regions [9]. A recent review showed that the pooled prevalence in Europe, North America and Asian countries in high or high‐middle income category ranged from 21·6 to 658·1 per one million donor units [10]. Consequently, HEV transmission through blood transfusion has become an emerging concern in industrialized countries.…”
Section: Introductionmentioning
confidence: 99%